Shakespeare as a Way of Life : Skeptical Practice and the Politics of Weakness - Kuzner, James (Book collections on Project MUSE., 2016)
"Shakespeare is worth reading, this book argues, because his works help us to make epistemological weakness into a way of life. I show how his works offer a means for coming to terms with basic uncertainties about freedom, the world's abundance, and the demands of love and social life"--